Inovasi Pembelajaran sebagai Strategi Peningkatan Kualitas Pendidikan di Indonesia - Sofiatul Khusnah (CV Omah Kreator, 2025)
Improving the quality of education is one of the main challenges in developing human resources in Indonesia. One prominent strategy to address this issue is the implementation of learning innovations that align with the dynamics of modern society and students’ needs. This study aims to analyze the role of learning innovation in enhancing educational quality through a library research approach. Data were collected from various scientific sources, including journals, books, and research reports discussing the relationship between learning innovation, educational quality, and teaching effectiveness. The results of the literature review indicate that learning innovation significantly contributes to increasing learning motivation, 21st-century skills, and overall learning outcomes. Moreover, the integration of technology and collaborative learning models creates a more active, creative, and meaningful learning environment. Therefore, learning innovation can be considered a key strategy in realizing a national education system that is adaptive, competitive, and characterized by the moral values of Pancasila within the framework of Society 5.0.